Упростить выражения: 1. [latex] \frac{1}{1+ctx} - \frac{1}{1-ctg x} [/latex] 2. [latex] \frac{1}{1-tg x} - \frac{1}{1+tg x} [/latex]
Упростить выражения:
1. [latex] \frac{1}{1+ctx} - \frac{1}{1-ctg x} [/latex]
2. [latex] \frac{1}{1-tg x} - \frac{1}{1+tg x} [/latex]
Ответ(ы) на вопрос:
1)1/(1+ctgx) -1/(1-ctgx)=(1-ctgx-1-ctgx)/(1-ctg²x)=-2ctgx/(1-ctg²x)=
=-2cosx/sinx :(sin²x-cos²x)/sin²x=2cosx/sinx*sin²x/(cos²x-sin²x)=sin2x/cos2x=tg2x
2)1/(1-tgx)-1/(1+tgx)=(1+tgx-1+tgx)/(1-tg²x)=2tgx/(1-tg²x)=tg2x
Не нашли ответ?
Похожие вопросы